Effect of the surface temperature of surface materials on thermal comfort: a case study of Iskenderun (Hatay, Turkey) - Bozdogan Sert, Elif; Kaya, Efdal; Adiguzel, Fatih; Cetin, Mehmet; Gungor, Senay; Zeren Cetin, Ilknur; Dinc, Yucel (Springer Science and Business Media LLC, 2021)
As a result of urbanization that started with the industrial revolution, high temperatures caused by surface materials in built areas cause the formation of urban heat islands. This situation adversely affects the livability of cities due to the thermal comfort or lack thereof. The surface temperatures of these widely used materials in a park located in the urban area of Iskenderun (Hatay, Turkey) were assessed in this study. The study was conducted in 3 stages in July 2019, one of the hottest months of the year in Iskenderun Community Park (the largest park on the borders of Iskenderun). The city itself is a coastal city with a Mediterranean climate. In the first stage, studies related to the subject were reviewed, and the points to be measured in the area were determined. It was taken into account that the measured points represented different surfaces in the park. In the second stage, the surface temperatures were measured 5 times in total during July using an infrared thermometer (TFA-ScanTemp330) from 12:00–13:00 with 3 repetitions from a height of 150 cm above the surface level. In the third stage, the data obtained was evaluated. The results of this study highlight the importance of the selection of surface materials in the development of healthy and livable cities. In regions where the Mediterranean climate prevails, the importance of increasing the presence of water bodies, grass areas, and plants (trees, bushes, and groundcover) due to their vital roles in reducing urban heat islands and increasing thermal comfort cannot be stressed enough.
Keywords: Atmospheric Science; Turkey; Iskenderun-Hatay; Thermal comfort; Heat island; Heat Islands; Temperature profile; Meteorology & Atmospheric Sciences; Hatay; Urban climate; Surface Materials; Meleagris gallopavo; Surface materials; Iskenderun; Surface Temperature; Surface temperature; Thermal Comfort; Boundary layer; Temperature effect; Land Surface Temperature; Urban Climate; 7. Clean energy; 11. Sustainability; 13. Climate action